2018
DOI: 10.1097/md.0000000000012470
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of gene polymorphisms of CD36 and ApoE with susceptibility of Alzheimer disease

Abstract: This research was aimed to explore correlation of gene polymorphisms of CD36 and ApoE with susceptibility of Alzheimer disease (AD).This study was a case–control study. Two hundred eleven AD hospitalized patients were selected as the AD group and 241 subjects were selected as the control group. PCR-RFLP was used to detect three loci (rs7755, rs3211956, and rs10499859) of CD36 gene and ApoE genotype. Chi-square test and univariate nonconditional logistic regression analysis were used to calculate the odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Concurrent to these and to our study, Garcia et al 54 Regarding the genotypic frequencies of the APOE gene, Zhou et al 40 and Demarchi et al 56 presented results very similar to those found in this meta-analysis. When evaluated together, they demonstrated that the Ԑ4 allele plays a role as a risk factor, while the Ԑ2 allele has a protective factor weight, agreeing with our results on its association with the genetic protection condition.…”
Section: Discussionsupporting
confidence: 91%
“…Concurrent to these and to our study, Garcia et al 54 Regarding the genotypic frequencies of the APOE gene, Zhou et al 40 and Demarchi et al 56 presented results very similar to those found in this meta-analysis. When evaluated together, they demonstrated that the Ԑ4 allele plays a role as a risk factor, while the Ԑ2 allele has a protective factor weight, agreeing with our results on its association with the genetic protection condition.…”
Section: Discussionsupporting
confidence: 91%
“…CD36 single nucleotide polymorphisms (SNP) have been linked to AD, some increasing the risk of AD [ 28 , 94 ] and others delaying disease onset [ 94 , 95 ]. In silico studies suggest that the protective SNP may suppress CD36-induced inflammation upon Aβ binding [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of one or two ApoE4 alleles implies a greater risk of LOAD, lower age of onset, more severe course of disease and poorer treatment response 13 , 14 . In addition to ApoE4, several other polymorphisms in various candidate genes have recently been identified as associated with LOAD 15 21 . The present study focuses on the polymorphisms of the candidate gene CD36 (“cluster of differentiation” 36).…”
Section: Introductionmentioning
confidence: 99%